Public International Law of Cyberspace - Kittichaisaree, Kriangsak (Cham : Springer International Publishing : Imprint: Springer, 2017)
This compact, highly engaging book examines the international legal regulation of both the conduct of States among themselves and conduct towards individuals, in relation to the use of cyberspace. Chapters introduce the perspectives of various stakeholders and the challenges for international law. The author discusses State responsibility and key cyberspace rights issues, and takes a detailed look at cyber warfare, espionage, crime and terrorism. The work also covers the situation of non-State actors and quasi-State actors (such as IS, or ISIS, or ISIL) and concludes with a consideration of future prospects for the international law of cyberspace. Readers may explore international rules in the areas of jurisdiction of States in cyberspace, responsibility of States for cyber activities, human rights in the cyber world, permissible responses to cyber attacks, and more. Other topics addressed include the rules of engagement in cyber warfare, suppression of cyber crimes, permissible limits of cyber espionage, and suppression of cyber-related terrorism. Chapters feature explanations of case law from various jurisdictions, against the background of real-life cyber-related incidents across the globe. Written by an internationally recognized practitioner in the field, the book objectively guides readers through on-going debates on cyber-related issues against the background of international law. This book is very accessibly written and is an enlightening read. It will appeal to a wide audience, from international lawyers to students of international law, military strategists, law enforcement officers, policy makers and the lay person.
1 Introduction: Perspectives of various stakeholders and challenges for international law -- 2 Jurisdiction and attribution of State responsibility in cyberspace -- 3 Regulation of the cyberspace and human rights -- 4 Cyber warfare -- 5 Application of the law of armed conflict, including international humanitarian law, in the cyberspace -- 6 Cyber espionage -- 7 Cyber crimes -- 8 Cyber terrorism -- 9 Future Prospects of International Law of Cyberspace.
Description based on publisher-supplied MARC data.
Keywords: International law; Law; Mass media; Public law; IT Law, Media Law, Intellectual Property; Public Law; Sources and Subjects of International Law, International Organizations